Osteoarticular Tuberculosis: A Secondary Manifestations to Tuberculous Pleural Effusion - Singh, Gurmeet; Rumende, Cleopas M; Setyohadi, Bambang (Indonesian Rheumatology Association, 2014)
Tuberculosis appears to be increasing throughout the world after years of continuous decline, despite the introduction of effective chemotherapy. This resurgence is related to the increasing number of patients immunocompromised by chemotherapeutic agents used to treat other diseases or Acquired Immunodeficiency Syndrome (AIDS); the appearance of multiple drug-resistant strains of tuberculosis, and aging population. Musculoskeletal tuberculosis arises from haematogenous seeding of the bacilli soon after the initial pulmonary infection.1 Osteoarticular TB can occur in the knee - one study found of 1074 cases, 8.3 percent - or 90 cases - affected the knee.2 The clinicalÂ symptoms are insidious onset, pain, swelling of the joint and limited range of movements. Investigations for suspected cases include: Mantoux test, radiological imaging, fine needle aspiration biopsy, surgical biopsy, bacteriological examination, histopathological examination, and polymerase chain reaction (PCR) of a suitable specimen. The mainstay of treatment is multidrug antitubercular chemotherapy. The main reason for poor outcome is delayed diagnosis.1 We report a case of osteoarticular manifestation of tuberculosis infection affecting the left knee presenting in a man with a history of tuberculosis pleural effusion. This case highlights, firstly, osteoarticular disease is always secondary to a primary lesion in the lung and, secondly, the diagnosis of tubercular arthritis can be challenging, particularly in the presence of confounding factors such as preexisting arthritis. Ethical approval was not required for this case study.